Permethrin induced oxidative stress and neurotoxicity on the freshwater beetle Laccophilus minutus. Issue 5 (28th May 2019) - Touaylia, Samir; Ali, Mezni; Abdellhafidh, Khazri; Bejaoui, Mustapha
ABSTRACT: Biomonitoring has become a useful tool in environmental risk assessment of anthropogenic activities releasing disturbing pollutants. Permethrin, used worldwide to control a wide range of pest insects, can threaten aquatic biota, potentially useful as precocious bioindicators in ecotoxicology. This study seeks to assess the acute toxicity permethrin to the freshwater beetle, its availability in water, as well as, its uptake. The acute toxicity of permethrin to non-target species was studied under laboratory conditions to assess its effect, after the exposure 48 h, on the freshwater beetle Laccophilus minitus considering changes in some enzymatic activities; a specific biomarker of neurotoxicity (acetylcholinesterase) and a non-specific biomarker of oxidative stress (superoxide dismutase and catalase). The rates of permethrin in water and insects were determined using gas chromatography. The low measured concentration of the pesticide 0.0013 μg/L didńt modify the SOD and CAT activities in comparison with controls, only the high concentrations (0.023 and 0.18 μg/L) induced a significant increase in the enzyme activity. A similar profile was recorded for the H2 O2 level. The permethrin treatment induced a drastic depletion of AChE activity. As outcomes, uptake at a low level (<6.8 ± 0.43 ng/g dry weight) showed to be the factor underlying the alterations in the beetles exposed to permethrin. Such findings provide information on the behaviour of permethrin within the environment and its biological target through its neurotoxicity and induction of oxidative stress in a freshwater beetle.